Changes in water state, distribution, and physico‐chemical properties of preserved kumquats during different processing methods. (11th May 2021) - Hu, Xiao; Wang, Rongrong; Xie, Qiutao; Ge, Keda; Li, Gaoyang; Fu, Fuhua; Ding, Shenghua; Shan, Yang
Abstract: Changes in water state, glass‐transition temperature ( T g ), microstructure, and some quality attributes of preserved kumquats after osmotic dehydration under atmospheric pressure or vacuum conditions followed by hot‐air drying were investigated. Low‐field nuclear magnetic resonance results showed that there was less immobilized water content in kumquats under vacuum impregnation with sugar (VSKs) versus that of kumquats under atmospheric pressure osmosis with sugar (ASKs). The freedom of water in kumquats under atmospheric pressure osmosis with sugar and then hot air‐drying (VS‐ADKs) was lower than that of kumquats under vacuum osmosis with sugar and then hot air‐drying (AS‐ADKs). Magnetic resonance imaging results revealed the water release. Sucrose intake produced a more pronounced depressing influence on the T g of VSKs than on that of the T g of ASKs. The T g of VS‐ADKs were lower than that of AS‐ADKs. Scanning electron microscopy displayed that the VSKs samples presented relatively compact tissue, but the ASKs exhibited the rupture of the cell cavities. The VS‐ADKs showed the more compact lamellar structure but the AS‐ADKs showed more loose fragments. The lightness of color in VSKs significantly decreased, while the redness and yellowness in ASKs diminished. High hardness and gumminess values were identified in VSKs and VS‐ADKs. Correlation analyses showed that hardness was positively correlated with T23 either in the ASKs or in the VSKs. Practical Application: Changes in water state, glass‐transition temperature ( T g ), microstructure, and some quality attributes of preserved kumquats after osmotic dehydration under atmospheric pressure or vacuum conditions followed by hot‐air drying were investigated. Low‐field nuclear magnetic resonance, magnetic resonance imaging, differential scanning calorimetry, scanning electron microscopy and so on were used as the intuitive and efficient methods. The differences in two immerse methods and the effects of drying on the properties of preserved kumquats were elucidated. These results were helpful to the control and assessments about the processing of preserved kumquats. Abstract : This research aimed to study changes in water state, glass‐transition temperature ( T g ), microstructure, and some quality attributes of preserved kumquats as well as the their correlation after osmotic dehydration under atmospheric pressure or vacuum conditions followed by hot‐air drying.